2017
DOI: 10.1038/aps.2016.164
|View full text |Cite
|
Sign up to set email alerts
|

Association between well-characterized lung cancer lncRNA polymorphisms and platinum-based chemotherapy toxicity in Chinese patients with lung cancer

Abstract: Platinum-based chemotherapy is the standard first-line treatment for most lung cancer patients. However, the toxicity induced by platinum-based chemotherapy greatly impedes its clinical use. Previous studies showed that long non-coding RNAs (lncRNAs) with over 200 nucleotides in length affect drug response and toxicity. In the present study, we investigated the association of well-characterized lung cancer lncRNA polymorphisms with platinum-based chemotherapy toxicity in Chinese patients with lung cancer. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 35 publications
1
53
0
1
Order By: Relevance
“…Another layer of interaction between these lncRNAs and miRNAs includes their regulatory role on the biogenesis of miRNAs. Taken together, a comprehensive approach is needed to assess contribution of these lncRNAs in the tumorigenesis Gong et al (2016) NSCLC 467 lung cancer patients rs6983267: reduced incidence of severe hematologic toxicity Gong et al (2017) Note. BM: bone marrow; PB: peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…Another layer of interaction between these lncRNAs and miRNAs includes their regulatory role on the biogenesis of miRNAs. Taken together, a comprehensive approach is needed to assess contribution of these lncRNAs in the tumorigenesis Gong et al (2016) NSCLC 467 lung cancer patients rs6983267: reduced incidence of severe hematologic toxicity Gong et al (2017) Note. BM: bone marrow; PB: peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…The only difference between lncRNAs and messenger RNAs is that lncRNAs lack protein coding potential . More than 40 lncRNAs have been reported to be associated with the initiation, progression, and drug resistance of LC . KCNQ1OT1, an lncRNA responsible for suppressing a cluster of genes in cis, has been shown to be involved in multiple cancers .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, several meta-analysis on aberration of H19 have been conducted thanks to the identi cation of numerous lncRNAs [23][24]. Though the results were contrary to many studies, a meta-analysis conducted by Lv et al revealed that rs217727 were uncorrelated to overall cancer risk [20].…”
Section: Discussionmentioning
confidence: 97%